Fitoquímica, atividades antimicrobiana e de inibição enzimática de Erythrina crista-galli (Fabaceae) e Valeriana polystachya (Caprifoliaceae) e obtenção de derivados de metabólitos de V. polystachya. - Ávila, Janaína Medeiros de (2018)
The disorders that affect the central nervous system and infectious diseases are among the pathologies that affect the world's population and grow more and more. Thus, the search for compounds that are potentially more effective and less cytotoxic to the human body is a constant in scientific research, mainly seeking in the nature bioactive substances that can be used in the treatment of diseases or that serve as prototypes for the development of new synthetic drugs. In this context, a phytochemical and pharmacological study was carried out with the species E. crista-galli (Fabaceae) and V. polystachya (Caprifoliaceae), native to the Pampa Biome. The pharmacological potential of these species was evaluated through antimicrobial activity tests against a collection of pathogenic microorganisms and enzymatic inhibition against the enzymes acetylcholinesterase (AChE) and prolyl oligopeptidase (POP). Plants of the genus Erythrina are large producers of erythrin alkaloids and used in folk medicine to treat various diseases due to its sedative, antidepressant, anticonvulsant properties and also in the treatment of antimicrobial infections, among others. A new (erythratidine N-oxide, 99) and five already known alkaloids were isolated from the stem bark of E. crista-galli. The antimicrobial action of this species was attributed mainly to the alkaloid erysotrine (15) that inhibited the growth of C.krusei fungus (MIC of 12.5 μg/ml). 15 and 99 showed inhibitors of POP activity with percentages of 77.0 (IC50 89.5 μM) and 50.6%, respectively. The genus Valeriana is known for its anxiolytic, sedative and sleep inducing effects. The bioguided isolation by the enzymatic assays of extracts and fractions prepared from the roots and rhizomes of V. polystachya, resulted in eighteen compounds, three of them unpublished in the literature, being the iridoids valtral D (102), IIHD-acevaltrate (104) and polistachin A (109). Results of enzyme inhibition revealed three POP, 102, valtrate (77) and baldrinal (49) inhibitors with IC50 of 5.3, 7.9 and 175.3 μM, respectively. The antimicrobial activity assays showed compounds with significant antimicrobial action (MICs 6.2-25 μg/ml) and antifungal (MICs between ˂ 1.5-25 μg/ml). In addition, some compounds were submitted to structural modifications, which resulted in ten derivatives, which were evaluated for antimicrobial action and enzymatic inhibitory activity against AChE and POP. A comparison of the chromatographic profile was also carried out between the V. polystachya and commercial V. officinalis species, showing that some extracts and fractions of both species have the same constituents.